From the Labor Question to the Murderous Economy: Catholic Approach to Economic Policy - Lóránd Ujházi; András Jancsó (Religions)
From his election, it was clear that Pope Francis advocated for the poor and the protection of creation. However, both areas are linked to ethical aspects of the economy. This paper demonstrates that although new aspects of Catholic economic ethics emerged with Pope Francis, they show a continuity with the Church’s social doctrine. Pope Francis is under fire from two directions. He is under attack from both economically minded conservatives and liberals. This paradox is interesting since these areas indicate Pope Francis’ teaching is partly static and dynamic. It is here that the dichotomy of continuity and progression is most visible. The Catholic Church theologically reflected on economics and then gradually in a transdisciplinary perspective. In this paper, we examine both methodologically and substantively the static elements of the Church’s teaching on the economy. We point to the slow but firm critical articulation of the Church’s opposition to the ethics of the capitalist economy. A qualitative method was used for the research, so primary and secondary Church documents and the theological and economic literature were applied. These were compared, opinions were contrasted, and a conclusion was drawn to justify the hypothesis.